New Iberian inscriptions from La Noguera (Lleida) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
This paper offers an edition of three unpublished Iberian inscriptions on earthenware. They were found at the archaeological sites of Tossal de la Ràpita and the Hereuet, from the territory of the Iberian tribe of the Ilergetes, and date from the Ibero-Roman period (the second to first century BCE). The texts are brief, as tends to be the case in this period, and it is not straightforward to determine their function, as not all three of them can be classified as owner’s marks (Besitzerangaben). The paper also presents a fourth document from the Hereuet site, a single-letter graffito.
Keywords: Iberian Epigraphy; Earthenware; Iberian Language; Graffiti; Tossal de la Ràpita; Hereuet